Computation of a subset of X-parameters using the adjoint method - Sidhu, Karanvir S. (2018)
Sidhu, K. S., Kassis, M. T., Toukhtarian, R., Tannir, D., & Khazaka, R. (2018, October). Computation of a subset of x-parameters using the adjoint method. In 2018 IEEE 27th Conference on Electrical Performance of Electronic Packaging and Systems (EPEPS) (pp. 61-63). IEEE.